2021
DOI: 10.5498/wjp.v11.i12.1267
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and mental well-being during COVID-19 pandemic

Abstract: The corona virus disease 2019 (COVID-19) pandemic has resulted in most nations deciding upon self-isolation and social distancing policies for their citizens to control the pandemic and reduce hospital admission. This review aimed at evaluating the effect of physical activity on mental well-being during the COVID-19 pandemic. It was concluded that the COVID-19 pandemic may lead to augmented levels of angiotensin-converting enzyme (ACE)-2 that led to cardiovascular and neurological disorders associated with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…MW is defined as the positive process of recognizing and making choices for a healthy and cheering life ( 17 ). In real life, MW may reflect as positive life experiences that consist of good social support, positive emotions, and satisfaction in life and work ( 18 ). For this particular group of medical staff, MW plays an essential role in developing and maintaining medical personnel's sympathy and compassion for patients and their dedication to the strict aspects of medicine ( 19 ), both of which are crucial to alleviating burnout.…”
Section: Introductionmentioning
confidence: 99%
“…MW is defined as the positive process of recognizing and making choices for a healthy and cheering life ( 17 ). In real life, MW may reflect as positive life experiences that consist of good social support, positive emotions, and satisfaction in life and work ( 18 ). For this particular group of medical staff, MW plays an essential role in developing and maintaining medical personnel's sympathy and compassion for patients and their dedication to the strict aspects of medicine ( 19 ), both of which are crucial to alleviating burnout.…”
Section: Introductionmentioning
confidence: 99%
“…We were happy to read the ingenious article by Abdelbasset et al [ 1 ], in which they illustrated the effect of physical activity on mental well-being during the coronavirus disease 2019 (COVID-19). The author not only elaborate the impact of physical activity on mental health through three sections: Mental health and community, neurological manifestations related to COVID-19, physical activity and mental health, but also conclude that the COVID-19 pandemic is correlated with angiotensin-converting enzyme-2, leading to related diseases.…”
Section: To the Editormentioning
confidence: 99%
“…Abdelbasset et al [ 1 ] concluded in the article that regular physical activities might improve mental health during the pandemic by reducing inflammatory responses. However, they also noted that overtraining or prolonged exercise may adversely induce mental disorders.…”
Section: To the Editormentioning
confidence: 99%
“…12 of World J of Psychiatry. The authors assert that the COVID-19 pandemic may have deleterious effects on physical and mental well-being, including a growing level of angiotensin-converting enzyme 2 (ACE-2), associated with highly inflammatory effects[ 1 ]. Furthermore, they highlighted the significance of regular physical activities that maintain individuals' mental health during the pandemic.…”
Section: To the Editormentioning
confidence: 99%